How the ‘Ulama Should Navigate through the TWAIL Movement: an Attasian Perspective - Fajri Matahati Muhammadin; Muhammad Raihan Sjahputra (International Law Discourse in Southeast Asia, 2026)
While the Third World Approaches to International Law (TWAIL) scholarship has rapidly developed over the past decade in the international law discourse, there have been some –albeit not very many—Islamic law contributions. Utilizing Al-Attas’s ‘Islamization’, which follows a different school of postcolonialism that gave birth to TWAIL, our research critically analyzes the extent to which Islamic scholarship can work with the TWAIL bandwagon and examines the prospects and challenges in how Islamic scholarship could and should navigate the Islam and international law discourse. We find that the ‘Ulama should navigate carefully in developing Islamic scholarship through the TWAIL movement.